The Contingencies of Emotional Intelligence on the Academic Performance of Trainee Teachers in selected Colleges of Education in Ghana - Commey-Mintah, Priscilla (Universitas Pendidikan Ganesha, 2023)
By understanding the contingencies of EI on AP, teacher education programs can be designed to foster the development of EI skills among trainee teachers, leading to more effective teaching practices and improved student outcomes. This study analyze the effect of EI (EI) on the academic achievement of aspiring English and math teachers. The study's teacher candidates were located in the two coed colleges of education. A quasi-experimental technique was adopted in the design of this investigation. Using the multistage sampling method, 648 second year prospective teachers were selected from the two colleges. EI Inventory were both adapted and used as the basis for the questionnaires that were created and given to all responders. The analysis is used A Multivariate Analysis of Variance (MANOVA). The results of the study showed a substantial difference in mathematics performance between the teacher candidates who were a part of the experimental group and those who were a part of the control group. On the other hand, there was no discernible difference in performance between the experimental and control groups in terms of English language. Hence, EI influenced trainees’ high performance in Mathematics, but it did not influence their performance in English Language. As a strategy to boost trainees’ EI, the implications and various recommendations have been made to both the administrative staff and tutors as well as the teacher trainees of the colleges of education.